Contrasting Fate of Western Third Pole's Water Resources Under 21st Century Climate Change - Su, Fengge; Pritchard, Hamish D.; Yao, Tandong; Huang, Jingheng; Ou, Tinghai; Meng, Fanchong; Sun, He; Li, Ying; Xu, Baiqing; Zhu, Meilin; Chen, Deliang (Earth's future, 2022)
Seasonal melting of glaciers and snow from the western Third Pole (TP) plays important role in sustaining water supplies downstream. However, the future water availability of the region, and even today's runoff regime, are both hotly debated and inadequately quantified. Here, we characterize the contemporary flow regimes and systematically assess the future evolution of total water availability, seasonal shifts, and dry and wet discharge extremes in four most meltwater‐dominated basins in the western TP, by using a process‐based, well‐established glacier‐hydrology model, well‐constrained historical reference climate data, and the ensemble of 22 global climate models with an advanced statistical downscaling and bias correction technique. We show that these basins face sharply diverging water futures under 21st century climate change. In RCP scenarios 4.5 and 8.5, increased precipitation and glacier runoff in the Upper Indus and Yarkant basins more than compensate for decreased winter snow accumulation, boosting annual and summer water availability through the end of the century. In contrast, the Amu and Syr Darya basins will become more reliant on rainfall runoff as glacier ice and seasonal snow decline. Syr Darya summer river‐flows, already low, will fall by 16%–30% by end‐of‐century, and striking increases in peak flood discharge (by >60%), drought duration (by >1 month) and drought intensity (by factor 4.6) will compound the considerable water‐sharing challenges on this major transboundary river. Plain Language Summary The western Third Pole (TP) is the most glacierized (>50% of the region) and snow‐concentrated areas in the region. Climate‐driven changes to the cryosphere in upper mountains in the TP have raised a major concern on the downstream water supply. However, the runoff regime and future water availability of the region are inadequately quantified. Here, we systematically assess the future evolution of runoff in total water availability, seasonal shifts, and dry and wet discharge extremes in four most meltwater‐dominated basins in the western TP by using a process‐based glacier‐hydrology model, well‐constrained historical and future climate data. We show that these basins face sharply diverging water futures under 21st century climate change. In the upper Indus and Yarkant, enhanced glacier melt will continue acting as a major water source in summer and annual water supply by the end of this century, especially under the highest emission scenario, but considerably increasing the extreme floods in the Indus. In contrast, the Syr Darya will face a declining annual water supply and increasing extreme spring floods and summer water shortages, as its glaciers retreat and snowmelt arrives earlier in the spring, further complicating the water resource management in this transboundary river. Key Points Contrasting patterns of water future are observed across four major mountain basins in the western Third Pole dictated by hydroclimatic regimes Glacier meltwater will continuously contribute to the increasing summer and annual water supplies in the upper Indus and Yarkant Syr Darya will face enhanced summer water shortage and increased wet and dry hydrological extremes due to shifted meltwater fluxes